Mythodology in Finance - Friend, Irwin (Journal of Finance, 1973)
Irwin Friend, Mythodology in Finance, The Journal of Finance, Vol. 28, No. 2, Papers and Proceedings of the Thirty-First Annual Meeting of the American Finance Association Toronto, Canada, December 28-30, 1972 (May, 1973), pp. 257-272